Erotic memoirs and postfeminism the politics of pleasure - Gwynne, Joel (Palgrave Macmillan, 2013)
"While books such as Belle de Jour's "The Intimate Adventures of a London Call Girl " and Catherine Millet's "The Sexual Life of Catherine M." captured the imagination of the reading public and marked the contemporary erotic memoir as a publishing phenomenon, the genre has received comparatively scarce scholarly attention. Through examining the cultural dominance of the figure of the 'phallic girl' (or 'ladette') in the early 21st century, this pioneering study explores the conflict that arises when the female-authored erotic memoir - a genre that holds enormous feminist potential - is co-opted by postfeminist cultural praxis. By analyzing the impact of the mainstreaming of pornography and the emergence of new communication technologies on conceptualizations of intimacy, agency and feminine sexual subjectivities, "Erotic Memoirs and Postfeminism" presents a broad critical survey of the genre and positions contemporary women's erotic memoirs as contradictory spaces in which female sexual autonomy is both actively celebrated and perniciously disavowed. The book also offers the first sustained critical analysis of a range of contemporary memoirs, including Abby Lee's "Girl with a One Track Mind", Melissa P.'s "One Hundred Strokes of the Brush Before Bed" and Tracy Quan's "Diary of a Manhattan Call Girl", amongst others." --Provided by publisher
Includes bibliographical references (p. [120]-124) and index
Agency -- Intimacy -- Pornography -- Transgression -- Conclusion
Keywords: Erotic literature / History and criticism; Autobiography / Women authors; Feminist literature / History and criticism; Feminismus; Erotische Literatur; Frauenliteratur